PAM-flexible Cas9-mediated base editing of a hemophilia B mutation in induced pluripotent stem cells - Takafumi Hiramoto; Yuji Kashiwakura; Morisada Hayakawa; Nemekhbayar Baatartsogt; Nobuhiko Kamoshita; Tomoyuki Abe; Hiroshi Inaba; Hiroshi Nishimasu; Hideki Uosaki; Yutaka Hanazono; Osamu Nureki; Tsukasa Ohmori (Communications Medicine, 2023)
Abstract Background Base editing via CRISPR-Cas9 has garnered attention as a method for correcting disease-specific mutations without causing double-strand breaks, thereby avoiding large deletions and translocations in the host chromosome. However, its reliance on the protospacer adjacent motif (PAM) can limit its use. We aimed to restore a disease mutation in a patient with severe hemophilia B using base editing with SpCas9-NG, a modified Cas9 with the board PAM flexibility. Methods We generated induced pluripotent stem cells (iPSCs) from a patient with hemophilia B (c.947T>C; I316T) and established HEK293 cells and knock-in mice expressing the patient’s F9 cDNA. We transduced the cytidine base editor (C>T), including the nickase version of Cas9 (wild-type SpCas9 or SpCas9-NG), into the HEK293 cells and knock-in mice through plasmid transfection and an adeno-associated virus vector, respectively. Results Here we demonstrate the broad PAM flexibility of SpCas9-NG near the mutation site. The base-editing approach using SpCas9-NG but not wild-type SpCas9 successfully converts C to T at the mutation in the iPSCs. Gene-corrected iPSCs differentiate into hepatocyte-like cells in vitro and express substantial levels of F9 mRNA after subrenal capsule transplantation into immunodeficient mice. Additionally, SpCas9-NG–mediated base editing corrects the mutation in both HEK293 cells and knock-in mice, thereby restoring the production of the coagulation factor. Conclusion A base-editing approach utilizing the broad PAM flexibility of SpCas9-NG can provide a solution for the treatment of genetic diseases, including hemophilia B.